Effect of Land Use on Organic Carbon Storage Potential of Soils with Contrasting Native Organic Matter Content - Sabina Yeasmin; Eshara Jahan; Md. Ashik Molla; A. K. M. Mominul Islam; Md. Parvez Anwar; Md. Harun Or Rashid; Sirinapa Chungopast (International Journal of Agronomy)
This study aimed to determine the impact of land use on organic carbon (OC) pools of soils with contrasting native organic matter (OM) content. Surface (0–15 cm) soils of four land uses (cropland, orchard, grassland, and fallow) were collected from four agroecological zones (AEZs) of Bangladesh with different OM content (AEZ-7: very low, −3: low, −9: medium, and −5: high). Bulk soils were physically fractionated into particulate and mineral associated OM (POM and MOM: >53 and <53 µm, respectively). Both bulk and fractionated soils were analyzed for OC and nitrogen (N). Among the land uses, undisturbed soils (grassland and fallow land) had significantly higher total OC (0.44–1.79%) than disturbed soils (orchard and cropland) (0.39–1.67%) in all AEZs. The distribution of OC and N in POM and MOM fractions was significantly different among land uses and also varied with native OM content. In all AEZs, cropland soils showed the lowest POM-C content (0.40–1.41%), whereas the orchard soils showed the highest values (0.71–1.91%). The MOM-C was highest (0.81–1.91%) in fallow land and lowest (0.53–1.51%) in orchard, and cropland had a moderate amount (0.70–1.61%). In croplands, distribution of a considerable amount of OC in the MOM pool was noticeable. These findings reveal that total OC in soils can be decreased with cultivation but does not inevitably indicate the loss of OC storage in the stable pool. Carbon storage potential of soils with both high- and low-native OM contents can be increased via proper land use and managements.